Comparative Study of Solar Panel Power Performance and Battery Charging Patterns of Lithium-Ion - Bavitra, Bavitra; Kusuma, Hollanda Arief; Refly, Septia; Guntara, Aldo (Journal of Telematics and Informatics, 2025)
New Renewable Energy (EBT) is an environmentally friendly energy source that can be continuously renewed. One of the EBT technologies that is widely used is solar panels, which utilize solar energy as an electrical resource. This research aims to analyze battery charging patterns based on using solar panels with capacities of 5WP, 10WP, and 20WP, as well as charging modules such as TP4056 and INA219 sensors to monitor voltage and amperage. The research results show that solar panels with a capacity of 20 WP have faster charging capabilities compared to solar panels with a capacity of 5 WP and 10 WP. The average battery charging time in sunny weather is around 3 hours, while the battery charging time in cloudy weather is around 6 hours. This shows that solar panels with higher capacity can increase the efficiency of the battery charging process. Keywords : New Renewable Energy, Solar Panels, Lithium-Ion Batteries, INA219 Sensors